Green Technology Innovation and Corporate Reputation: Key Drivers of ESG and Firm Performance - Chen, Xiyi; Lakkanawanit, Pankaewta; Suttipun, Muttanachai; Swatdikun, Trairong; Huang, Shi-Zheng (Emerging Science Journal, 2024)
The purpose of this study is to investigate the impact of Environmental, Social, and Governance (ESG) performance and firm performance within China's manufacturing sector, with a novel focus on the mediating effect of green technology innovation and the moderating influence of corporate reputation. Using a 2011-2022 dataset from A-share listed manufacturing companies on the Shanghai and Shenzhen Stock Exchanges, the study employs multiple regression analysis with a two-way fixed-effects model to examine these relationships. Findings indicate that robust ESG practices significantly enhance company performance, mediated by green technological innovation. However, a negative moderating effect of corporate reputation suggests that higher corporate reputation weakens the ESG-financial performance relationship. Further analyses reveal that privately-owned firms, those in China's eastern region, and environmentally sustainable industries benefit most from strong ESG initiatives. This study addresses the challenge of disentangling key variables by analyzing their interconnected effects. The findings fill a gap in the existing literature by contributing to a deeper understanding of the relationship between ESG and corporate success, particularly through the mediating role of innovation and the moderating influence of reputation. Additionally, the study provides practical recommendations for managers and policymakers to enhance ESG strategies, promote growth, and support sustainable development. Doi: 10.28991/ESJ-2024-08-06-021 Full Text: PDF